Organizational Directors' Perceptions About Awareness of Services Among Their Employees and the Older Adults They Serve. (June 2020) - Teixeira-Poit, Stephanie M.; Napier, Ariana; Carr, Christine; Williams, Jessica; Pulliam, Paul
Objectives: This study explores the extent to which directors of organizations perceive that (a) older adults are aware of and interested in using services, and (b) their employees are aware of complementary services in the community and are willing to coordinate care or refer older adults to these services.Method: We conducted 41 qualitative semistructured interviews with organizational directors who provide services to older adults.Results: Directors perceived that not only older adults but also some providers were unaware of services in the community. Directors reported that some older adults felt stigmatized and were unwilling to use services, but services providers implemented strategies to overcome these barriers.Discussion: Understanding the perceptions of organizational directors may help identify opportunities for older adults to learn about community services and for providers to better coordinate care.